Gametophytic Selection in Arabidopsis thaliana Supports the Selective Model of Intron Length Reduction - Seoighe, Cathal; Gehring, Chris; Hurst, Laurence D (PLOS Genetics, 2005)
Why do highly expressed genes have small introns? This is an important issue, not least because it provides a testing ground to compare selectionist and neutralist models of genome evolution. Some argue that small introns are selectively favoured to reduce the costs of transcription. Alternatively, large introns might permit complex regulation, not needed for highly expressed genes. This “genome design” hypothesis evokes a regionalized model of control of expression and hence can explain why intron size covaries with intergene distance, a feature also consistent with the hypothesis that highly expressed genes cluster in genomic regions with high deletion rates. As some genes are expressed in the haploid stage and hence subject to especially strong purifying selection, the evolution of genes in Arabidopsis provides a novel testing ground to discriminate between these possibilities. Importantly, controlling for expression level, genes that are expressed in pollen have shorter introns than genes that are expressed in the sporophyte. That genes flanking pollen-expressed genes have average-sized introns and intergene distances argues against regional mutational biases and genomic design. These observations thus support the view that selection for efficiency contributes to the reduction in intron length and provide the first report of a molecular signature of strong gametophytic selection.